Individual characteristics moderate listening effort in noisy classrooms - Chiara Visentin; Matteo Pellegatti; Maria Garraffa; Alberto Di Domenico; Nicola Prodi (Scientific Reports, 2023)
Abstract Comprehending the teacher’s message when other students are chatting is challenging. Even though the sound environment is the same for a whole class, differences in individual performance can be observed, which might depend on a variety of personal factors and their specific interaction with the listening condition. This study was designed to explore the role of individual characteristics (reading comprehension, inhibitory control, noise sensitivity) when primary school children perform a listening comprehension task in the presence of a two-talker masker. The results indicated that this type of noise impairs children’s accuracy, effort, and motivation during the task. Its specific impact depended on the level and was modulated by the child’s characteristics. In particular, reading comprehension was found to support task accuracy, whereas inhibitory control moderated the effect of listening condition on the two measures of listening effort included in the study (response time and self-ratings), even though with a different pattern of association. A moderation effect of noise sensitivity on perceived listening effort was also observed. Understanding the relationship between individual characteristics and classroom sound environment has practical implications for the acoustic design of spaces promoting students’ well-being, and supporting their learning performance.